Silicon Valley sizzle or fizzle? [employment situation].
Though employment among US electrical and electronics engineers had grown modestly in the second quarter of 2004, employment of computer scientists and software engineers dropped rather precipitously. In Silicon Valley itself, employment was still far below its 2001 peak and not much above 1995 levels. Office vacancies remained near a record high, and venture capitalism investment was still very sluggish. This paper looks at some leading indicators to get a more up-to-date sense of the real mood at Silicon Valley today. These indicators are the day care enrollments, BMW sales, hotel occupancies, and restaurant reservations in the area.
Keywords: BMW sales; Silicon Valley; Day care enrollments; Employment; Hotel occupancies; Restaurant reservations